Biomimicry of the Hawk Moth, Manduca sexta (L.), Produces an Improved Flapping-Wing Mechanism - Kenneth Moses; Mark Willis; Roger Quinn (Biomimetics, 2020)
Flapping-wing micro air vehicles (FWMAVs) that mimic the flight capabilities of insects have been sought for decades. Core to the vehicle’s flight capabilities is the mechanism that drives the wings to produce thrust and lift. This article describes a newly designed flapping-wing mechanism (FWM) inspired by the North American hawk moth, Manduca sexta. Moreover, the hardware, software, and experimental testing methods developed to measure the efficiency of insect-scale flapping-wing systems (i.e., the lift produced per unit of input power) are detailed. The new FWM weighs 1.2 grams without an actuator and wings attached, and its maximum dimensions are 21 × 24 × 11 mm. This FWM requires 402 mW of power to operate, amounting to a 48% power reduction when compared to a previous version. In addition, it generates 1.3 gram-force of lift at a flapping frequency of 21.6 Hz. Results show progress, but they have not yet met the power efficiency of the naturally occurring Manduca sexta. Plans to improve the technique for measuring efficiency are discussed as well as strategies to more closely mimic the efficiency of the Manduca sexta-inspired FWM.